2019
DOI: 10.1186/s40479-018-0098-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbid borderline personality disorder on inpatient treatment for bulimia nervosa: analysis of routine data

Abstract: BackgroundA substantial rate of patients with bulimia nervosa (BN) also suffer from Borderline personality disorder (BN + BPD). It is widely unknown how these comorbid patients with BN + BPD present and respond to inpatient treatment. Aims of the study were to examine (1) specific characteristics of patients with BN + BPD at admission, discharge, and during treatment, and (2) differential effects of inpatient treatment for BN vs. BN + BPD.MethodWe analyzed routine data of inpatients admitted for the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
4
9
0
Order By: Relevance
“…Given the same average treatment duration for patients with AN and AN+BPD in our study, it remains to be investigated whether the comorbid patients would have benefitted from prolonged treatment. However, a similar investigation from our clinic examined the influence of BPD on inpatient treatment for bulimia nervosa found comparable patterns of symptom severity and outcome despite prolonged treatment for comorbid patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the same average treatment duration for patients with AN and AN+BPD in our study, it remains to be investigated whether the comorbid patients would have benefitted from prolonged treatment. However, a similar investigation from our clinic examined the influence of BPD on inpatient treatment for bulimia nervosa found comparable patterns of symptom severity and outcome despite prolonged treatment for comorbid patients [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neacsiu, Fang, Rodriguez and Rosenthal ( 2018 ) evidenced that problems in emotion regulation are differentially connected to suicidal behaviors. Finally, Al‐Dajani, Uliaszek and Hamdullahpur ( 2019 ) showed that, cross‐sectionally, the relationship between emotion dysregulation and suicide ideation was significantly moderated by the belief of suicide as an escape, and longitudinally the latter moderated only the relationship between lack of clarity and suicide ideation.…”
Section: Introductionmentioning
confidence: 99%
“…interpersonal difficulties, unstable self-image and self-esteem, marked impulsivity, dysfunctional defense mechanisms, and emotion dysregulation might play a relevant role in determining response to ED treatment (Martinussen et al, 2017;Voderholzer et al, 2021). In line with previous empirical evidence, cooccurring Cluster B symptoms in an ED patient may mark greater severity, and thus potentially predict a poorer outcome and less symptomatic change (Steiger et al, 1993;Hessler et al, 2019). Cluster B personality characteristics have also been related to other therapeutic variables, such as a history of psychiatric hospitalization for an ED or other condition (Westen and Harnden-Fischer, 2001) and a greater risk of discharge against medical advice and re-admission following intensive ED treatment (Wildes et al, 2011).…”
Section: Discussionmentioning
confidence: 58%